Outgrower programme: Floriculture technical exchange in Fiji - Kurukuruvakatini, Keresi (Technical Centre for Agricultural and Rural Cooperation, 2018)
To promote floriculture, South Sea Orchids (SSO) has established an outgrower programme in Fiji, which provides a temperate climate and market links to Asia, Australia and New Zealand. The aim of the project was to foster female empowerment across Fiji by teaching women how to grow flowers through workshops and information booklets. The floriculture industry has improved as a result of more marketable produce being grown, and women have been able to create their own sources of income to spend on their own priorities.